Design, fabrication and performance analysis of TTD structures for S-band active phased array RF beamforming networks - Ahmet Hastürk; Nursel Akçam; Tayfun Okan (MANAS: Journal of Engineering)
In this study an eight-channel active analog beamforming structure is designed and developed in subsystems by using a Applied Wave Research (AWR) simulation program. This structure works in S-band and contains true-time-delay (TTD) systems. The simulation results and the results obtained from the manufactured structure are compared. In the comparison, the TTD values for different time delay steps and phase difference measurements between channels are analyzed and interpreted. The test results show that desired performance is obtained from the designed and manufactured PCB. However, it is observed that feeding each antenna element with single channel beamforming board would be more appropriate.